La disfunción familiar y su influencia en el rendimiento escolar en los niños del Centro de Desarrollo Infantil “Kids Place” - Leiva Álvarez, Paola Alexandra (2020)
The research addresses a problem related to the incidence of family dysfunction in school performance among children of the Children's Development Center "Kids Place" for which it was proposed as a general objective to develop a training program for the fulfillment of the functions of the families; to achieve it, the non-experimental methodology, a qualitative approach, and the deductive, bibliographic, dialectical, historical, empirical, statistical, interview, survey, observation, and triangulation methods were used as instruments resulting in the training program for parents for the fulfillment of its functions; it was validated through user criteria and a socialization workshop which allows supporting that the training program has had a significant impact and an absolute reception within the Center of Child Development, as well as in the other Institutions. Through its implementation, students can be helped in a positive way to improve their school performance as well as in their coexistence and insertion to their family nucleus.